Sex-specific effects of tea consumption and salt intake on metabolic syndrome and its components among oilfield workers - Liu, Haobiao; Zhang, Tianxiao; Jia, Lianxu; Yang, Bowei; Zhang, Dianchao; Han, Jing (Frontiers in Nutrition, 2025)
ObjectivesThe prevalence of metabolic syndrome (MetS) has been rising globally, posing a significant public health challenge. While numerous studies have examined the risk factors for MetS, limited research has explored the combined effects of tea consumption and salt intake on MetS, particularly from a sex-specific perspective.MethodsThe Chinese Diabetes Society criteria were adopted to identify MetS patients, and the logistic regression analysis was employed to explore the association between tea consumption, salt intake, and MetS. The odds ratio (OR) and corresponding 95% confidence interval (CI) were calculated.ResultsAmong the 2,721 oilfield workers, 28.30% were diagnosed with MetS, with males displaying a higher prevalence than females across all individual components. Higher tea consumption was associated with an increased risk of MetS and specific components in males, whereas salt intake demonstrated a more selective impact, primarily affecting triglyceride levels in males and waist circumference in females. When considering the combined effects, males with high tea consumption and high salt intake exhibited the highest risk of MetS (OR = 1.83, 95% CI: 1.30 to 2.57, p < 0.001) compared to non-tea drinkers with low salt intake. However, no statistical significance was observed between different combinations of tea consumption and salt intake among females.ConclusionThis study highlights the sex-specific impact of tea consumption and salt intake on MetS, with a significant association observed only in males. The combined exposure to high tea consumption and high salt intake may exacerbate MetS risk, emphasizing the need for tailored dietary recommendations. Further prospective studies are warranted to confirm these findings.